Language Style in Romantic Movies - Juliana Dewi, Ni Made Ayu; Ediwan, I Nyoman Tri; Suastra, I Made (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p01, 2020)
This study aims to find out the types of language style in romantic movies and what is the dominant type of language style that found in romantic movies. The data were taken from romantic movie entitled The Last Song (2010) and Midnight Sun (2018). The data were collected by using documentation method by applying qualitative audio-visual materials technique.In analysingthe data, this study used both qualitative method and quantitative method and for the presenting data and analysis, formal and informal method were used. The data were analyzed using theory of language style by Joos (1976) and theory of context situation byHymes (1974). The result shows that all types of language style are found in Romantic movie. In The Last Song (2010) movie could be found frozen style, formal style, consultative style, intimate style and casual style. Meanwhile in Midnight Sun (2018) movie there are only formal style, consultative style, intimate style and casual style. The dominant type found in romantic movies is intimate style, while the least is frozen style.